Association of cardiovascular risk using non-linear heart rate variability measures with the framingham risk score in a rural population - Jelinek, Herbert F.; Imam, Hasan M.; Al-Aubaidy, Hayder; Khandoker, Ahsan H. (Frontiers in Physiology, 2013)
Cardiovascular risk can be calculated using the Framingham cardiovascular disease (CVD) risk score and provides a risk stratification from mild to very high CVD risk percentage over 10 years. This equation represents a complex interaction between age, gender, cholesterol status, blood pressure, diabetes status and smoking. Heart rate variability (HRV) is a measure of how the autonomic nervous system modulates the heart rate. HRV measures are sensitive to age, gender, disease status such as diabetes and hypertension and processes leading to atherosclerosis. We investigated whether HRV measures are a suitable, simple, noninvasive alternative to differentiate between the four main Framingham associated CVD risk categories. In this study we applied the tone-entropy (T-E) algorithm and complex correlation measure (CCM) for analysis of heart rate variability obtained from 20 minute ECG recordings and correlated the HRV score with the stratification results using the Framingham risk equation. Both entropy and CCM had significant analysis of variance (ANOVA) results (F172, 3 = 9.51; <0.0001). Bonferroni post hoc analysis indicated a significant difference between mild, high and very high cardiac risk groups applying tone-entropy (p<0.01). CCM detected a difference in temporal dynamics of the RR intervals between the mild and very high CVD risk groups (p<0.01). Our results indicate a good agreement between the T-E and CCM algorithm and the Framingham CVD risk score, suggesting that this algorithm may be of use for initial screening of cardiovascular risk as it is noninvasive, economical and easy to use in clinical practice.